(5) \[ \begin{array}{l} 3 x^{2}-3(x-1)=4(2 x+1)+3 \\ x^{2}=x \end{array} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To solve the equation, let's first simplify the first equation step by step: Starting with: \[ 3 x^{2}-3(x-1)=4(2 x+1)+3 \] Distributing \( -3 \) and \( 4 \): \[ 3 x^{2} - 3x + 3 = 8x + 4 + 3 \] \[ 3 x^{2} - 3x + 3 = 8x + 7 \] Now, rearranging everything to one side gives us: \[ 3 x^{2} - 3x - 8x + 3 - 7 = 0 \] \[ 3 x^{2} - 11x - 4 = 0 \] Next, we can apply the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 3 \), \( b = -11 \), and \( c = -4 \): \[ x = \frac{11 \pm \sqrt{(-11)^2 - 4 \cdot 3 \cdot (-4)}}{2 \cdot 3} \] \[ x = \frac{11 \pm \sqrt{121 + 48}}{6} \] \[ x = \frac{11 \pm \sqrt{169}}{6} \] \[ x = \frac{11 \pm 13}{6} \] Calculating the two potential solutions: 1. \( x = \frac{24}{6} = 4 \) 2. \( x = \frac{-2}{6} = -\frac{1}{3} \) So, the solutions are: \[ x = 4 \quad \text{and} \quad x = -\frac{1}{3} \] Now turning to our second equation: \[ x^{2}=x \] This can be rewritten as: \[ x^{2} - x = 0 \] Factoring gives: \[ x(x - 1) = 0 \] From this factored form, we see that \( x = 0 \) or \( x = 1 \). In summary, the solutions to the first equation are \( x = 4 \) and \( x = -\frac{1}{3} \), while the solutions to the second equation are \( x = 0 \) and \( x = 1 \).